Self-standing MOF-derived LiCoO2 nanopolyhedron on Au-coated copper foam as advanced 3D cathodes for lithium-ion batteries. (June 2020) - Lin, Jia; Zeng, Chenghui; Wang, Limei; Pan, Yingying; Lin, Xiaoming; Reddy, R. Chenna Krishna; Cai, Yuepeng; Su, Cheng-Yong
Graphical abstract: The hexagonal layered LiCoO2 in-situ growth on 3D Au-coated copper foam substrate (denoted as LCO@ACF) was obtained by novel MOF-derived (lithium ion doped ZIF67) synthetic strategy. Ascribed to the advantages of large specific capacity, high porosity, boosted electrochemical conductivity, protective carbon layer, and "Electron-Li + shared capacitor" mechanism, the as-synthesized self-standing 3D LCO@ACF electrode delivers distinguished cycling and superior rate capability. Highlights: LiCoO2 in-situ growth on 3D Au-coated copper foam substrate was fabricated by novel MOF-derived synthetic strategy. This self-standing 3D LCO@ACF electrode delivers distinguished cycling and superior rate capability. "Electron-Li + shared capacitor" mechanism, kinetics and quantitative analyses of lithium storage behavior were conducted. Abstract: Considering the imperious challenge of the state-of-the-art lithium ion batteries (LIBs) with the development of portable electronics, the widely commercialized LiCoO2 cathode for LIBs cannot satisfy the emerging need for flexible devices. Acknowledgedly, self-standing LiCoO2 cathodes immobilised on 3D substrates are still confronted with challenge. Herein, for the first time, we report an original fabrication strategy for the hexagonal layered LiCoO2 in-situ growth on 3D Au-coated copper foam substrate (denoted as LCO@ACF), among which the ACF (confirmed by angle resolved X-ray photoelectron spectroscopy, ARXPS) serves as not only the backbone and electron pathway for charge delivery and storage, but supports the active materials. Accordingly, the lithium ions doped ZIF67 (named as Li@ZIF67) was firstly synthesized by a facile microwave-assisted route and further in-situ growth on the ACF substrate (Li@ZIF67@ACF), which acts as a self-sacrificial MOF templates, and finally annealed under the optimal condition. Ascribed to the advantages of the structure of MOF precursor and 3D substrate, the as-synthesized self-standing 3D LCO@ACF electrode possesses large specific capacity, high porosity, and boosted electrochemical conductivity. As LIBs half-cell at 25 °C, the LCO@ACF electrode delivers a distinguished cycling stability of 136.4 mA h g −1 at 2 C after 600 cycles, as well as excellent rate capability of 111.7 mA h g −1 at 15 C, which are further deciphered by ex-situ Raman analyses, CV measurements, and "Electron-Li + shared capacitor" mechanism. To expand the material application scope, the 3D LCO@ACF materials were evaluated under harsh testing conditions by cycling at a higher temperature of 50 °C, and successfully constructed into the LCO@ACF//Graphite LIBs full cell, among which LCO@ACF exhibits superior full cell electrochemical performance as for LIBs cathode. The strategy for synthesizing 3D self-standing MOF-derived cathode provides prospects for designing promising high-performance flexible LIBs cathodes.